Ghrelin Receptor Deficiency does not Affect Diet-Induced Atherosclerosis in Low-Density Lipoprotein Receptor-Null Mice - Habegger, Kirk M.; Grant, Erin; Pfluger, Paul T.; Perez-Tilve, Diego; Daugherty, Alan; Bruemmer, Dennis; Tschoep, Matthias H.; Hofmann, Susanna (Frontiers in Endocrinology, 2011)
Objective: Ghrelin, a stomach-derived, secreted peptide, and its receptor (growth hormone secretagogue receptor, GHSR) are known to modulate food intake and energy homeostasis. The ghrelin system is also expressed broadly in cardiovascular tissues. Since ghrelin has been associated with anti-inflammatory and anti-atherogenic properties, but is also well known to promote obesity and impair glucose metabolism, we investigated whether ghrelin has any impact on the development of atherosclerosis. The hypothesis that endogenous ghrelin signaling may be involved in atherosclerosis has not been tested previously Methods and Results: We crossed ghrelin receptor knockout mice (GHSr-/-) into a low-density lipoprotein receptor-null (Ldlr-/-) mouse line. In this model, atherosclerotic lesions were promoted by feeding a high-fat, high-cholesterol Western-type diet for 13 months, following a standard protocol. Body composition and glucose homeostasis were similar between Ldlr-/- and Ldlr/GHSR -/- ko mice throughout the study. Absence or presence of GHSr did not alter the apolipoprotein profile changes in response to diet exposure on an LDLRko background. Atherosclerotic plaque volume in the aortic arch and thoracic aorta were also not affected differentially in mice without ghrelin signaling due to GHSR gene disruption as compared to control LDLRko littermates. In light of the associations reported for ghrelin with cardiovascular disease in humans, the lack of a phenotype in these loss-of- function studies in mice suggests no directly functional role for endogenous ghrelin in either the inhibition or the promotion of diet-induced atherosclerosis. Conclusions: These data indicate that, surprisingly, the complex and multifaceted actions of endogenous ghrelin signaling on the cardiovascular system have minimal direct impact on atherosclerotic plaque progression as based on loss-of-function in a mouse model of the disease.